The effect of focus of attention during a single bout of resistance exercise on plantarflexion torque complexity and cortical drive in older adults : a randomized controlled trial - Marques, Tiago José Santos (My University, 2025)
Introduction: Ageing is accompanied by impairments in neuromuscular function, contributing to reduced force control, increased muscle co-contraction during gait, and diminished adaptability, ultimately increasing the risk of falling. Resistance training and attentional focus strategies have independently been proposed as potential modulators of these deficits, yet their combined effect remains unclear, especially in older adults. The present study investigated how different attentional focus instructions during a single bout of plantarflexion resistance training influence force control and the underlying neurophysiological mechanisms in this population. Methods: 23 participants (≥ 60 years old) were screened and homogeneously randomized into internal, external, or visual (distal) external focus groups after a familiarization session. In the evaluation session, neuromuscular and cortical drive measures were obtained before and after a single standardized seated calf raise resistance training bout. Results: No group-related differences were observed. However, acute pre- to post-training effects emerged across all groups, including reduced maximal force production, increased torque variability (coefficient of variation), and decreased corticospinal inhibition. Torque complexity and intracortical measures remained unchanged. Conclusion: These findings suggest that attentional focus strategies applied during a single resistance training session are not sufficient to modify force control or cortical mechanisms in older adults. Nonetheless, the observed neuromuscular fatigue and corticospinal modulation highlight this population’s acute adaptations to a single resistance training session.

Introdução: O envelhecimento é acompanhado por défices na função neuromuscular, contribuindo para uma redução no controlo da força, aumento da co-contração muscular durante a marcha e diminuição da adaptabilidade, aumentando, em última análise, o risco de quedas. O treino de força e as estratégias de foco de atenção têm sido propostas, de forma independente, como potenciais moduladores destes défices, mas o seu efeito combinado permanece pouco claro, especialmente em adultos mais velhos. O presente estudo investigou como diferentes instruções de foco de atenção durante uma única sessão de treino de força dos flexores plantares influenciam o controlo da força e os mecanismos neurofisiológicos subjacentes nesta população. Métodos: 23 participantes (≥ 60 anos) foram selecionados e aleatoriamente distribuídos de forma homogénea entre os grupos de foco interno, externo ou externo visual (distal), após uma sessão de familiarização. Na sessão de avaliação, foram obtidas medidas neuromusculares e de ativação cortical antes e após uma sessão única de treino de força padronizada de elevação dos calcanhares sentado. Resultados: Não foram observadas diferenças entre grupos. No entanto, surgiram efeitos agudos do pré- para o pós-treino em todos os grupos, incluindo redução na produção máxima de força, aumento da variabilidade do torque (coeficiente de variação) e diminuição da inibição corticoespinhal. A complexidade do torque e as medidas intracorticais permaneceram inalteradas. Conclusão: Estes resultados sugerem que estratégias de foco de atenção aplicadas durante uma única sessão de treino de força não são suficientes para modificar o controlo da força ou os mecanismos corticais em adultos mais velhos. No entanto, a fadiga neuromuscular observada e a modulação corticoespinhal evidenciam as adaptações agudas desta população a uma sessão de treino de força.
Dissertação para obtenção do grau de mestre na Escola Superior de Saúde Egas Moniz
Keywords: Focus of attention; Older adults; Resistance training; Torque complexity; Transcranial magnetic stimulation